Atypical hemolytic uremic syndrome: a nationwide Colombian pediatric series (2023)
Background Atypical hemolytic uremic syndrome (aHUS) is a rare complement-mediated kidney disease with genetic predisposition and represents up to 10% of pediatric hemolytic uremic syndrome (HUS) cases. Few studies have evaluated aHUS in Latin American population. We studied a Colombian pediatric cohort to delineate disease presentation and outcomes. Methods A multicenter cohort of 27 Colombian children with aHUS were enrolled between 2010 to 2019. Patients were grouped by age at onset. Clinical features were compared using analysis of variance (ANOVA) and Fisher exact tests. Renal biopsy was performed on six patients who were suspected of having other renal diseases before aHUS diagnosis. Results Most patients were male (70%). The onset of aHUS occurred frequently before age 4 years (60%) and followed gastroenteritis as the main triggering event (52%). Age groups were comparable in clinical presentation, disease severity, treatment, and outcomes. Pulmonary involvement (67%) was the main extrarenal manifestation. A higher frequency was observed in the 1–7 age group (p = 0.01). Renal biopsies were as follows: three had membranoproliferative glomerulonephritis (MPGN) type I, one MPGN type III, one C3-glomerulonephritis, and one rapidly progressive glomerulonephritis. Genetic screening was available in five patients and identified 2xCFHR5, 2xMCP, and 1xADAMTS-13/THBD mutations. A total of 15 relapses were seen, of which 8 (72%) occurred in the 1–7 age group. The renal outcome was not significantly different regardless of age group. Conclusion In our cohort, we observed a relatively high frequency of extrarenal involvement at first presentation represented by pulmonary manifestations. The renal prognosis at initial presentation was worse than in previous reports.